Sistem Informasi Layanan Pengadilan Agama Boyolali Berbasis Android - Restu Winaldi Wibisono; Donna Setiawati; Fera Tri Wulandari (JITU : Journal Informatic Technology And Communication, 2023)
The Religious Court or often referred to as the Religious Court is one of the government institutions that carries out judicial functions in the field of religious law issues, especially Islam, such as marriage problems and inheritance issues in Islam. The religious court as a government institution is currently working to create information transparency and improve public services to the public. There are several services on the Boyolali Religious Court, this research focuses on making the Boyolali Religious Court Information System based on Android using a flutter framework from the client side, for the admin using the web created using codeigniter flramework. Data collection methods include interviews, observation, literature study and questionnaires. The method uses the extreme programming method (XP). The result of this research is the construction of a web-based and android-based Boyolali Religious Court Service Information System which informs what services are available at the Boyolali Religious Court and features checking the Divorce Certificate online via androd.